Winning the Unwinnable War: America's Self-Crippled Response to Islamic Totalitarianism - Journo, Elan (Lexington Books, 2009)
Eight years after 9/11 and in the shadow of two protracted U.S. military campaigns in the Middle East, the enemy is not only undefeated but emboldened and resurgent. What went wrong_and what should we do going forward? Winning the Unwinnable War shows how our own policy ideas led to 9/11 and then crippled our response in the Middle East, and it makes the case for an unsettling conclusion: By subordinating military victory to perverse, allegedly moral constraints, Washington's policy has undermined our national security. Owing to the significant influence of Just War Theory and neoconservatism, the Bush administration consciously put the imperative of shielding civilians and bringing them elections above the goal of eliminating real threats to our security. Consequently, this policy left our enemies stronger, and America weaker, than before. The dominant alternative to Bush-esque idealism in foreign policy_so-called realism_has made a strong comeback under the tenure of Barack Obama. But this nonjudgmental, supposedly practical approach is precisely what helped unleash the enemy prior to 9/11. The message of the essays in this thematic collection is that only by radically re-thinking our foreign policy in the Middle East can we achieve victory over the enemy that attacked us on 9/11. We need a new moral foundation for our Mideast policy. That new starting point for U.S. policy is the moral ideal championed by the philosopher Ayn Rand: rational self-interest. Implementing this approach entails objectively defining our national interest as protecting the lives and freedoms of Americans_and then taking principled action to safeguard them. The book lays out the necessary steps for achieving victory and for securing America's long-range interests in the volatile Middle East.